MANAJEMEN KEGIATAN EKSTRAKURIKULER DALAM MENGEMBANGKAN MINAT DAN BAKAT PESERTA DIDIK DI MADRASAH ALIYAH SWASTA AL WASHLIYAH 22 TEMBUNG - Muhammad Nasri Sitorus; Fitri Yulia; Putri Syahri (STKIP Subang, 2026)
ABSTRACT This study aims to describe the management of extracurricular activities in developing students’ talents and interests at Madrasah Aliyah Al Washliyah Tembung. The research focuses on planning, organizing, implementing, evaluating, and developing extracurricular programs. A qualitative approach with a case study method was employed. Data were collected through interviews with the school principal, vice principals for curriculum and student affairs, extracurricular coaches, and active students from Paskibra, Marching Band, and Scout activities. The findings reveal that extracurricular planning is carried out systematically based on students’ needs, interests, and talents, taking into account the academic calendar and available resources. Organizing is implemented through clear task distribution among coaches, activity coordinators, and students. Activities are conducted regularly and structured, synchronized with the academic schedule to avoid disrupting learning processes. Evaluation is performed periodically to assess program effectiveness and provide feedback for improvement. Furthermore, extracurricular development includes enhancing the quality of trainers, adding facilities, and innovating programs relevant to current trends. Extracurricular activities at Madrasah Aliyah Al Washliyah Tembung have been proven to improve students’ social skills, leadership, and self-confidence, while optimizing their non-academic potential. The study concludes that extracurricular management in the school has been effective, adhering to educational management principles, particularly the POAC theory (Planning, Organizing, Actuating, Controlling). However, challenges such as limited funding and facilities still require further attention to maximize students’ talent and interest development.